2006
DOI: 10.1504/ijsn.2006.010825
|View full text |Cite
|
Sign up to set email alerts
|

Wireless networking security: open issues in trust, management, interoperation and measurement

Abstract: The pervasive availability and wide usage of wireless networks with different kinds of topologies, techniques and protocol suites have brought with them a need to improve security mechanisms. The design, development and evaluation of security techniques must begin with a thorough analysis of the requirements and a deeper understanding of the approaches that are practical within the system constraints. In this paper, we investigate the recent advances in wireless security from theoretical foundations to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 77 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Within a mix zone area where a user is untraceable, all the users' identities in the same zone will be mixed. This results in an indiscernible identity [65]. Lastly, to effectively mitigate wireless security and privacy issues, awareness on cybersecurity must be instilled into the public so that every wireless network user knows how to protect themselves from wireless attack.…”
Section: Unique Solution To Prevent Active and Passive Attacksmentioning
confidence: 99%
“…Within a mix zone area where a user is untraceable, all the users' identities in the same zone will be mixed. This results in an indiscernible identity [65]. Lastly, to effectively mitigate wireless security and privacy issues, awareness on cybersecurity must be instilled into the public so that every wireless network user knows how to protect themselves from wireless attack.…”
Section: Unique Solution To Prevent Active and Passive Attacksmentioning
confidence: 99%
“…However, none of them considers AES overhead in their analysis. Many related security research can be found in [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Related Workmentioning
confidence: 99%
“…Wireless ad hoc networks (WANETs) are decentralized wireless networks, which do not have any preexisting infrastructure like wired networks, due to routers and access points [1]. WANETs can be further classified into two categories mobile ad hoc networks (MANETs) and Vehicular Ad Hoc Networks (VANETs).…”
Section: Introductionmentioning
confidence: 99%